2011
DOI: 10.1111/j.1439-0426.2011.01737.x
|View full text |Cite
|
Sign up to set email alerts
|

Report on first time reproductive success from full life-cycle culture of Kaluga sturgeon females (Huso dauricus)

et al.

Abstract: Ten females of Kaluga sturgeon (Huso dauricus; 73.8 ± 6.49 kg, total length 204.5 ± 12.8 cm) matured for the first time after a full life-cycle in captivity. Absolute gonad biomass was 8.4 ± 1.3 kg per female and relative fecundity 11.2 ± 1.6%, at maturation stage IV. These fish were induced to spawn by injection of hormone LHRH-A2 at a dosage of 10 lg kg )1 . Male Kaluga was injected one time at 5 lg kg )1 and milt was stripped 16 h after injection of LHRH-A2. Water temperature was about 16 ± 1°C during the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Li W et al . (2011) artificially inseminated Huso dauricus by the semi‐dry method and found that the fertilization and hatching rates were above 80%. The reason for the low fertilization rate in this study may be that the spermatozoa and ovaries of P. argenteus parents do not mature at the same time and there is a certain time lag.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li W et al . (2011) artificially inseminated Huso dauricus by the semi‐dry method and found that the fertilization and hatching rates were above 80%. The reason for the low fertilization rate in this study may be that the spermatozoa and ovaries of P. argenteus parents do not mature at the same time and there is a certain time lag.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) studied the viability of seed production of Macrognathus pancalus reared under confined conditions, and the fertilization rate and hatching rate were over 90%. Li W et al (2011) artificially inseminated Huso dauricus by the semi-dry method and found that the fertilization and hatching rates were above 80%. The reason for the low fertilization rate in this study may be that the spermatozoa and ovaries of P. argenteus parents do not mature at the same time and there is a certain time lag.…”
Section: Discussionmentioning
confidence: 99%